Архіви України в міжнародних та міжрегіональних програмах збереження культурної спадщини: досвід та перспективи - Папакін, Г. (Архіви України, 2008)
The article is focused on Ukrainian practices and participation in international and cross-regional programs of physical preservation of archives as a part of cultural heritage in 1991–2006. The author states that cooperation of Ukraine and other countries would be beneficial within the strict national legislative framework, with all stakeholders’ interests observed and balanced.